1260Contribution of risk factors to disease burden in Australia in 2018. (2nd September 2021) - Gourley, Michelle
Abstract: Background: The Australian Burden of Disease Study 2018 estimated the burden due to 219 diseases and injuries and 40 risk factors (attributable burden). Attributable burden is the amount of health loss that would be prevented if exposure to the risk factor had been avoided or reduced to the lowest possible exposure. Methods: Attributable burden was estimated for 2003, 2011, 2015 and 2018 using comparative risk assessment methodology. Estimates of exposure to risk factors were sourced from Australian survey data and used with global measures of effect size to estimate population attributable fractions (PAFs). Results: In 2018, 37% of the burden of disease in Australia could have been prevented by reducing or avoiding exposure to the modifiable risk factors included in the study. The leading five risk factors contributing to total burden were: tobacco use (8.6%), overweight & obesity (8.4%), dietary risks (5.4%), high blood pressure (5.1%) and alcohol use (4.5%). While tobacco use remains the leading risk factor causing burden, the gap between tobacco use and overweight & obesity has almost closed. The burden attributable to most risk factors was higher in males than in females. The lowest socioeconomic group experienced greater burden compared with the highest group for all risk factors. Conclusions: Addressing modifiable risk factors could prevent up to 37% of disease burden in Australia. Key messages: In 2018, 37% of the burden of disease could have been prevented. Tobacco use and overweight & obesity were the leading risk factors.